Preferensi Petani terhadap Kriteria Varietas Cabai Keriting Merah yang Dibudidayakan (Kajian di Kecamatan Semin, Kabupaten Gunung Kidul, Daerah Istimewa Yogyakarta) - Penggalih, Paksi Mei; Nabila, Nailan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
One of the horticultural commodities that are in great demand by almost all Indonesian people is red curly chili. For producers, in creating varieties and selling chili seeds, ideally in line with the preferences of chili farmers. The purpose of this study was to determine the preferences of red curly chili farmers. This research was conducted in Semin District, Gunung Kidul Regency, Special Region of Yogyakarta from June to July 2023. The sample selection method was purposive sampling, namely farmers who grow red curly chilies in the area. The type of data is primary, with the data collection method through direct interviews with farmers. Data analysis using Conjoint Analysis. The results showed that the five main priorities of farmers' preferences in cultivating red curly chilies were 1) the color of the chilies, namely red, 2) the shape of the chilies, which was elongated, 3) the age of harvesting chilies ranging from 80-100 days, 4) the size of the chilies 10-15 cm , 5) there is shortening of the chili plants starting from the 3rd branch. Furthermore, farmers tend to like chilies that are resistant to Anthracnose/Patek disease, the fruit has tortuous curvatures, plant height is around 100-150 cm, the plant performance is wide, the chili's shelf life is 7-10 days, the chilies fall off, the chili skin thickness is medium, the surface of the chili is smooth, the taste of the chili is spicy, and it is resistant to grapyak caterpillars and fruit flies. Kata kunci: chili, farmer, preference